Optimization of chemical admixture for concrete on mortar performance tests using mixture experiments - (:unkn) unknown (VILNIUS GEDIMINAS TECHNICAL UNIV PRESS, TECHNIKA, 2008)
The ready mixed concrete sector has been developing rapidly as a result of technological improvements, especially for skyscrapers and high constructions. Concrete design is hard and expensive job, moreover it takes too much time. It must confirm some special conditions such as durability and strength during its life cycle period. The selection of appropriate chemical admixtures is very important criterion to achieve the desired specifications for concrete. Therefore, in this study via mixture experiments, which has been developed rapidly in the last 50 years, a mixture design is constructed to examine the effects of dosage and components on the response variables indicating mortar performance. The target is to reach optimum point by obtaining maximum compressive strength on mortar with minimum cost of admixture. The component proportions are determined in each dosage level using desirability function and cost calculation is made for these component proportions. A graphical method is suggested for examining effects of dosage and mixture components on the response variables. The comments are made for the whole system using the suggested graphical method.
Keywords: chemical admixture; concrete design; desirability function; mixture design; mixture experiments; Scheffe polynomials; trace plot; CEMENT